PENGARUH KUALITAS PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFE KO.WE.COK DI SOLO - Kumrotin, Evi Laili; Susanti, Ari (Universitas Malikussaleh, 2021)
Product quality is a condition of labor, tasks, processes and an environment with changing conditions for the fulfillment of daily needs. Which in this case shows that the quality of the product has a function that can satisfy consumers in meeting consumer product needs. The object of this research is Cafe KO.WE.COK Solo. To determine whether or not a product quality, price and service quality affect customer satisfaction is the aim of this study. Using a questionnaire including primary data to analyze the data in this study. The sample taken in this study were 50 respondents and the sampling technique used was accidental sampling. The results of the study used the validity test method, reliability test, classical assumption test, multiple linear regression test, T test, F test, and the coefficient of determination test. From the calculation of the validity test the value of r results is greater (>) than the value of r table, so the validity test has valid results. From the calculation of reliability it is said to be reliable or reliable. From the research results, the classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test. Shows normality test results and does not occur multicollinearity and heteroscedasticity does not occur. The multiple linear regression test shows that these variables can increase customer satisfaction at the KO.WE.COK Solo cafe. In the F test, the three X variables are said to be jointly influencing and related to customer satisfaction.